Cardiovascular safety of revefenacin, a once-daily, lung-selective, long-acting muscarinic antagonist for nebulized therapy of chronic obstructive pulmonary disease: Evaluation in phase 3 clinical trials. (August 2019) - Donohue, James F.; Feldman, Gregory; Sethi, Sanjay; Barnes, Chris N.; Pendyala, Srikanth; Bourdet, David; Crater, Glenn
Abstract: The cardiovascular safety of revefenacin, an anticholinergic indicated for the maintenance treatment of patients with chronic obstructive lung disease (COPD), was evaluated in phase 3 trials in patients with moderate to very severe COPD. No clinically meaningful changes in 12-lead electrocardiogram recordings were observed with up to 52 weeks of once-daily revefenacin 88 or 175 μg. In a pooled analysis of Studies 0126 and 0127, the incidence of prolonged QT interval corrected for heart rate using the Fridericia correction formula (QTcF; >450 msec) for revefenacin 88 μg (n = 23, 5.6%) and revefenacin 175 μg (n = 23, 5.9%) was similar to that for placebo (n = 22, 5.3%). In Study 0128, the incidence of prolonged QTcF was similar in the revefenacin 175 μg (n = 25, 7.7%) and tiotropium (n = 26, 7.3%) groups and lower in the revefenacin 88 μg (n = 15, 4.2%) group. There were four major adverse cardiac events (MACEs) in Study 0126 (one, two, and one in the placebo, revefenacin 88 μg, and revefenacin 175 μg groups, respectively), no MACEs in Study 0127 and 26 MACEs in Study 0128 (9, 10 and 7 in the revefenacin 88 μg, revefenacin 175 μg and tiotropium groups, respectively). In Study 0128, only one MACE was considered possibly/probably related to revefenacin (atrial fibrillation in the revefenacin 175 μg group). Thus, revefenacin may provide beneficial nebulized therapy for patients with COPD without further elevating their risk of cardiovascular events.